Analisis Nilai-nilai Pendidikan Karakter dalam Serial Kartun Boruto: Naruto Next Generation - Annisa, Khoirun; Zufriady , Zufriady; Syahrilfuddin, Syahrilfuddin (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
Instilling the values of character education is very urgent to do for the progress of a nation. The problem in this research is the cartoon series Boruto: Naruto Next Generation in which there are various kinds of character education values that can be used as media in character education cultivation, but these values have not been able to be captured properly by the audience of the cartoon series. The results of this study are 1) to determine the values of character education in the cartoon series Boruto: Naruto Next Generation (Chunin Exam Arc). The results of this study indicate that the cartoon series Boruto: NarutoNext Generation is a cartoon series that can be used as an alternative in character education learning. This is because in this cartoon series there are character education values. There are six kinds of character values, 1) hard work, 2) respect for achievement, 3) responsibility, 4) logical, critical, creative, and innovative thinking, 5) love of reading, and 6) love of peace.